Organizational strategic intuition for high performance: The role of knowledge-based dynamic capabilities and digital transformation - Yaninee Songkajorn; Somnuk Aujirapongpan; Kritsakorn Jiraphanumes; Kanittha Pattanasing (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This study investigated the role of organizational strategic intuition (OSI) and relationships with knowledge-based dynamic capabilities (KBDCs), digital transformation (DT), and high-performance organizations (HPOs). This quantitative study used a questionnaire to collect data from chief executive officers (CEOs) and engineers of various companies in the auto parts industry, a crucial income-generator for Thailand. Partial least squares structural equation modeling, which assesses reflective and structural models, was adopted to test the hypotheses. The findings revealed significant influences among the six pairs of constructed relationships. Indeed, investigations found in this study indicated that (1) KBDCs had a positive effect on DT; (2) KBDCs and DT had a positive effect on OSI; and (3) KBDCs, DT, and OSI had a positive effect on HPOs. The analytical results of this empirical study also provided information to expand the knowledge of strategic intuition (SI). The practical contribution of this study is a consolidated comprehensive framework of OSI that contained vital insights for CEOs, policymakers, and practitioners to support the creation of OSI, leading to better strategic decisions.
Keywords: 650; digital transformation; high-performance organization; knowledge-based dynamic capabilities; open innovation; organizational strategic intuition; strategic intuition